Encouraging Quality Regulation: Theories and Tools - Kevin Guerin (New Zealand Government, The Treasury, 2003)
Achieving good regulatory outcomes normally requires high quality design, implementation and review of the regulatory regime. Major regulatory theories focus on concepts such as the public interest, the role of interest groups, and regulatory capture to explain why regulations come into existence. Regulatory design, however, exists at two levels. Downstream design involves creating a regime to give the appropriate incentives to firms and consumers. Upstream design seeks to incentivise regulators themselves to create and operate high quality regulatory regimes. This paper focuses on the latter. The OECD has undertaken a major programme on regulatory governance to ensure quality in the design and implementation of regulations. Such measures are now widespread. New Zealand has gradually implemented these approaches including Regulatory Impact Analysis (RIA) in its decision- making processes. These measures are supported, and to some degree required, by increased interaction with Australian practices through institutions such as the Council of Australian Governments and the obligations of Trans-Tasman Mutual Recognition Arrangement. Achieving full integration of best practice that creates an environment for consistently delivering high quality regulation requires a broad and sustained focus on design, capability, incentives and follow-up. New Zealand has attempted over the last decade to improve regulatory outcomes by focusing on the incentives on regulators. There is still scope for further improvement. Sustained progress on a number of mutually supporting initiatives, with continued reinforcement of the underlying messages and careful building of the necessary institutions and practices is required for continued improvement.
Keywords: H0; L51; 330; Quality regulation; Regulatory Quality; Regulatory Reform; Regulatory Capture